The two facets of receptor tyrosine kinase in cardiovascular calcification—can tyrosine kinase inhibitors benefit cardiovascular system? - Masbuchin, Ainun Nizar; Widodo,; Rohman, Mohammad Saifur; Liu, Ping-Yen (Frontiers in Cardiovascular Medicine, 2022)
Tyrosine kinase inhibitors (TKIs) are widely used in cancer treatment due to their effectiveness in cancer cell killing. However, an off-target of this agent limits its success. Cardiotoxicity-associated TKIs have been widely reported. Tyrosine kinase is involved in many regulatory processes in a cell, and it is involved in cancer formation. Recent evidence suggests the role of tyrosine kinase in cardiovascular calcification, specifically, the calcification of heart vessels and valves. Herein, we summarized the accumulating evidence of the crucial role of receptor tyrosine kinase (RTK) in cardiovascular calcification and provided the potential clinical implication of TKIs-related ectopic calcification. We found that RTKs, depending on the ligand and tissue, can induce or suppress cardiovascular calcification. Therefore, RTKs may have varying effects on ectopic calcification. Additionally, in the context of cardiovascular calcification, TKIs do not always relate to an unfavored outcome—they might offer benefits in some cases.